2010
DOI: 10.1186/2042-6410-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hypothalamic astrocyte response to estradiol stimulation

Abstract: BackgroundReproductive functions controlled by the hypothalamus are highly sexually differentiated. One of the most dramatic differences involves estrogen positive feedback, which leads to ovulation. A crucial feature of this positive feedback is the ability of estradiol to facilitate progesterone synthesis in female hypothalamic astrocytes. Conversely, estradiol fails to elevate hypothalamic progesterone levels in male rodents, which lack the estrogen positive feedback-induced luteinizing hormone (LH) surge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…In cell culture models, estradiol is shown to promote signaling mechanisms that increase intracellular Ca 2+ concentrations and corresponding astrocyte Ca 2+ dependent functions (Chaban et al, 2004; Kelly and Ronnekleiv, 2009). While not tested in our preparation, estradiol was reported to increase cytoplasmic Ca 2+ release in cultured hypothalamic astrocytes collected from both males and females but not in females with estrogen receptor knockout (Kuo et al, 2010). It has also been shown that elevated intracellular Ca 2+ stimulates astrocyte mitochondrial metabolism to maintain vital energy resources during the first few hours after ischemia.…”
Section: 3 Discussionmentioning
confidence: 84%
“…In cell culture models, estradiol is shown to promote signaling mechanisms that increase intracellular Ca 2+ concentrations and corresponding astrocyte Ca 2+ dependent functions (Chaban et al, 2004; Kelly and Ronnekleiv, 2009). While not tested in our preparation, estradiol was reported to increase cytoplasmic Ca 2+ release in cultured hypothalamic astrocytes collected from both males and females but not in females with estrogen receptor knockout (Kuo et al, 2010). It has also been shown that elevated intracellular Ca 2+ stimulates astrocyte mitochondrial metabolism to maintain vital energy resources during the first few hours after ischemia.…”
Section: 3 Discussionmentioning
confidence: 84%
“…Certain functions of astrocytes also present sex-dimorphic characteristics, such as glutamate uptake, the response to glutamate (Hsu et al, 2001;Morizawa et al, 2012), the response to cannabinoids (Lopez-Gallardo et al, 2012) or even the response to gonadal hormones (Arnold et al, 2008;Gulinello and Etgen, 2005;Kuo et al, 2010a;Zhang et al, 2002). Sex also influences the response of astrocytes to harmful stimuli such as prenatal or neonatal stress (Garcia-Caceres et al, 2010;Llorente et al, 2009Llorente et al, , 2008Lopez-Gallardo et al, 2012), exposure to toxins (Santos-Galindo et al, 2011) and to environmental contaminants (Astiz et al, 2014;Miller et al, 2010;Sundar Boyalla et al, 2011) or deprivation of oxygen and glucose (Liu et al, 2008(Liu et al, , 2007 (Figure 1).…”
Section: Neurobiology Of Astrogliamentioning
confidence: 99%
“…The increase in the activity of StAR and TSPO leads to an increase in progesterone synthesis in the astrocyte (Chaban et al, 2004;Chen et al, 2014;Dewing et al, 2007;Kuo et al, 2010b;Micevych et al, 2007). In female rodents, the production of progesterone by hypothalamic astrocytes in response to estradiol is involved in the initiation of luteinizing hormone surge and the subsequent ovulation (Kuo et al, 2010a). In addition to play this role in the control of reproduction, the synthesis of progesterone by astrocytes in response to estradiol may also be involved in the regulation of many aspects of brain function under physiological and pathological conditions (Melcangi et al, 2014).…”
Section: Astrocytes As a Source Of Estradiol And Progesteronementioning
confidence: 99%
“…Astrocytes from both males and females express estrogen receptor (ER) α, ERβ, the transmembrane ER, GPR30, and progesterone and androgen receptors (Azcoitia et al, 1999; Pawlak et al, 2005b; Arnold et al, 2008; Duncan et al, 2013; Kuo et al, 2010b) and estradiol facilitates the synthesis of progesterone in astrocytes (Micevych et al, 2007; Chaban et al, 2004). In addition, astrocytes were found to be the most steroidogenic brain cells producing several neurosteroids, such as progesterone, testosterone, and estradiol, and expressing enzymes involved in hormone synthesis, including aromatase (Zwain and Yen, 1999).…”
Section: Astrocytes Produce and Respond To Gonadal Hormonesmentioning
confidence: 99%